Bilateral asymmetries of humeral retroversion in junior and collegiate tennis players - Hannah, D. C.; Scibek, J. S.; Carcia, C. R.; Phelps, A. L. (Journal of Athletic Training, 2021)
Context Overhead-throwing athletes consistently display substantial bilateral differences in humeral retroversion (HRV). However, evidence is limited regarding HRV asymmetries in tennis players despite similarities between the overhead throw and tennis serve.